Beautiful and Difficult Years of Adolescence. Aristocratic Education in Late Imperial Russia - Vydra, Zbyněk (My University, 2022)
The article focuses on the education and upbringing of aristocrats in late imperial Russia (the 1850s–1917). It is based primarily on sources of a personal nature (non-published and published memoirs and diaries). Their analysis shows the main elements, continuity and discontinuity in the education of boys and girls from aristocratic families during their adolescence, i. e. from the age of twelve/thirteen to sixteen/eighteen. Unlike childhood, for which homeschooling was typical, the period of adolescence was significantly more dynamic. The aristocratic education was more influenced by state educational reforms, growing civic awareness, and various ideas about the best preparation for future life and a career. Aristocratic families chose from among elite noble schools, private lycées, or state public schools gymnasiums). The nobility’s approach to education was slowly being democratised. More and more aristocrats studied at state public schools (gymnasiums). At the same time, criticism of the conservative conditions of the education system was heard from the ranks of the aristocracy.
Krásná a složitá léta dospívání. Vzdělávání aristokracie v pozdně-carském Rusku
Keywords: Imperial Russia; aristocracy; history of education; history of everyday life; carské Rusko; aristokracie; dějiny vzdělávání; dějiny každodennosti